Natural disaster and nuclear crisis in Japan : response and recovery after Japan's 3/11 - Kingston, Jeff, 1957- (London ; New York : Routledge, 2012)
"The March 2011 earthquake and tsunami in Japan plunged the country into a state of crisis. As the nation struggled to recover from a record breaking magnitude nine earthquake and a tsunami that was as high as 38 meters in some places, news trickled out that Fukushima had experienced meltdowns in three reactors. These tragic catastrophes claimed some 20,000 lives, initially displacing some 500,000 people and overwhelming Japan's formidable disaster preparedness. This book brings together the analysis and insights of a group of distinguished experts on Japan to examine what happened, how various institutions and actors responded and what lessons can be drawn from Japan's disaster. The contributors, many of whom experienced the disaster first hand assess the wide-ranging repercussions of this catastrophe and how it is already reshaping Japanese culture, politics, energy policy, and urban planning. This book is essential reading for anyone seeking an understanding of the events of March 2011 in Japan and the wider consequences for the future of the country and the rest of the world."--Publisher's description.
Tohoku diary: reportage on the Tohoku disaster / Gerald Curtis -- Recovery in Tohoku / John F. Morris -- From Kobe to Tohoku: the potential and the peril of a volunteer infrastructure / Simon Avenell -- Civil society and the triple disasters: revealed strengths and weaknesses / Yuko Kawato, Robert Pekkanen, Yutaka Tsujinaka -- Social media in disaster Japan / David H. Slater, Nishimura Keiko and Love Kindstrand -- March 11, 2011 online: comparing Japanese newspaper websites and international news websites / Leslie M. Tkach-Kawasaki -- Networks of power: institutions and local residents in post-Tohoku Japan / Daniel P. Aldrich -- Hard choices: Japan's post-Fukushima energy policy in the 21st century / Paul J. Scalise -- Fukushima and the political economy of power policy in Japan / Andrew DeWit, Iida Tetsunari, and Kaneko Masaru -- Dealing with disaster / Peter Duus -- The politics of natural disaster, nuclear crisis and recovery / Jeff Kingston -- Friends in need: 'Operation Tomodachi' and the politics of US military disaster relief in Japan / Chris Ames and Yuiko Koguchi-Ames -- The economic fallout: Japan's post-3/11 challenges / Kenneth Neil Cukier -- Ageing society, health issues and disaster: assessing 3/11 / Junko Otani -- Thousand-year event: towards reconstructing communities / Riccardo Tossani -- Can post-3/11 Japan overcome 20 years of drift? / Kazuhiko Togo.
Includes bibliographical references and index.
AAL
Keywords: Tohoku earthquake and tsunami, Japan, 2011.; Nuclear power plants -- Accidents -- Japan -- Fukushima-ken.; Disaster relief -- Japan